Effect of Supplementation of Aloe vera (Aloe barbadensis miller) Powder on Performance of Broiler Chicken - J. Ashar,; S. M. Bhalerao,; A. V. Khanvilkar,; A. S. Kadam,; G. S. Sonawane,; A. K. Barate,; S. B. Nagargoje,; S. R. Kharde,; B.C. Andhale, (Indian Journal of Animal Nutrition, 2022)
Poultry stands as one of the fastest growing segments among the agricultural sectors in India today. In India, the Poultry industry has been developing most dynamically and is a rapidly expanding segment of livestock economy. Immunity, health and production are some important factors that challenge the growth of poultry industry. Nutrition is the most important factor that affects the productive performance and economics related to poultry sector project. Phytogenic feed additives or PFA’s, are included into animal feed to improve the productivity via the improvement in digestibility, absorption of nutrients and elimination of resident pathogens in the animal intestinal tract. Aloe vera is one among many plants that has a great medicinal potential. The present study was undertaken to study the effects of supplementation of Aloe vera leaf powder in feed of broiler birds. An experiment trial was conducted on total 240 straight run day-old commercial broiler chicks of Vencobb 430Y strain at the college poultry farm of Krantisinh Nana Patil College of Veterinary Science, Shirwal, dist. Satara for a period of 42 days (six weeks). The broilers from groups T1, T2 and T3 were given graded levels of Aloe vera powder. Each treatment group was divided into four replicates and each replicate had 15 birds. The findings of our investigation revealed that there was no significant effect (P>0.05) of feeding Aloe vera powder on weekly body weight, weekly body weight gain, weekly feed intake and weekly feed conversion ratio in broiler birds.